POVERTY REDUCTION IN THE STRATEGY OF THE NEW UZBEKISTAN: PROBLEMS AND SOLUTIONS - X.N. Akhmedov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article discusses the problems of poverty reduction in the context of the Strategy of the new Uzbekistan, as well as ways to solve them.